2022
DOI: 10.1108/imds-04-2021-0254
|View full text |Cite
|
Sign up to set email alerts
|

Transactive memory system and green innovation: a cross-level mediation of social network

Abstract: PurposeThe aim of this study was to investigate the impact of the transactive memory system (TMS) on green innovation and examine the mediation role of the social network at all hierarchical levels.Design/methodology/approachThree hypotheses were examined by performing regression analyses on survey data from manufacturing firms in China. Especially, the nested sets of data from 389 individual observations nested in 53 work teams, including individual level and collective level have been investigated.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…They highlighted that when the centrality is higher, the resource elements of team members will be negatively correlated with knowledge innovation. This is because the combination of knowledge elements with other elements is limited: the core knowledge elements whose science and technology have been exhausted are in excessive concentration and high integration, and further combination will minimize the marginal benefit (Xiao et al, 2022). This finding remains even though Manteli et al (2014) demonstrated that there is a positive, significant correlation between centrality measures and transactive memory systems processes.…”
Section: Effects Of Network Density and Centrality On Transactive Mem...mentioning
confidence: 99%
“…They highlighted that when the centrality is higher, the resource elements of team members will be negatively correlated with knowledge innovation. This is because the combination of knowledge elements with other elements is limited: the core knowledge elements whose science and technology have been exhausted are in excessive concentration and high integration, and further combination will minimize the marginal benefit (Xiao et al, 2022). This finding remains even though Manteli et al (2014) demonstrated that there is a positive, significant correlation between centrality measures and transactive memory systems processes.…”
Section: Effects Of Network Density and Centrality On Transactive Mem...mentioning
confidence: 99%
“…They have tried to determine how individual knowledge can be transformed into collective knowledge and stored as shared meaning and mental models (Krull et al. , 2022; Xiao et al. , 2022).…”
Section: State Of the Artmentioning
confidence: 99%
“…Against this backdrop, the researchers of knowledge management area have turned their attention to the organizational strategies that can support knowledge sharing and the creation of knowledge repositories. They have tried to determine how individual knowledge can be transformed into collective knowledge and stored as shared meaning and mental models (Krull et al, 2022;Xiao et al, 2022). Some have focused on the classical knowledge sharing strategies (e.g.…”
Section: Organizational Strategies To Avoid Corporate Amnesiamentioning
confidence: 99%